Epidemiology and Risk Factors for Cervical Cancer - Patiyus Agustiansyah; Rizal Sanif; Siti Nurmaini; Irfannuddin; Legiran (HM Publisher, 2021)
Cervical cancer in Indonesia in 2018 ranks second in cancer in women in Indonesia with an incidence rate of 348.809 cases with a mortality rate of nearly 60% of the incidence, namely 207.210 deaths. Deaths from cervical cancer are projected to continue to increase and are estimated to reach 12 million deaths by 2030 if not treated properly. The incidence of cervical cancer in Indonesia is estimated to have 180.000 new cases per year and the death rate is thought to reach 75% in the first year. This death is mainly associated with the majority of newly diagnosed patients who are already at an advanced stage (70% of cases) and are already at the terminal stage at the time of diagnosis.